2020
DOI: 10.1371/journal.pone.0232972
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides isolated from Cordyceps Sinensis contribute to the progression of NASH by modifying the gut microbiota in mice fed a high-fat diet

Abstract: Various dietary fibers are considered to prevent obesity by modulating the gut microbiota. Cordyceps sinensis polysaccharide (CSP) is a soluble dietary fiber known to have protective effects against obesity and related diseases, but whether these effects induce any side effects remains unknown. The function and safety of CSP were tested in high-fat diet (HFD)-feding C57BL/6J mice. The results revealed that even though CSP supplementation could prevent an increase in body weight, it aggravated liver fibrosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…The changes in the gut microbiota are related with speci c metabolic states, such as obesity [40]. Actinobacteria was positively correlated with obesity [41], the high level of Actinobacteria aggravated the disorder of the intestinal ora and contributed to the progression from obesity to the related diseases [42]. Saccharibacteria are prominent in the oral cavity, and increased abundance of Saccharibacteria is correlated with the development of periodontitis [43] and in ammatory bowel disease [44].…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the gut microbiota are related with speci c metabolic states, such as obesity [40]. Actinobacteria was positively correlated with obesity [41], the high level of Actinobacteria aggravated the disorder of the intestinal ora and contributed to the progression from obesity to the related diseases [42]. Saccharibacteria are prominent in the oral cavity, and increased abundance of Saccharibacteria is correlated with the development of periodontitis [43] and in ammatory bowel disease [44].…”
Section: Discussionmentioning
confidence: 99%
“…CSP1-2 fraction also demonstrated an antihypertensive effect on spontaneously hypertensive rats (SHR) by stimulating the secretion of vasodilator NO, decreasing the level of ET-1, epinephrine, noradrenaline, and angiotensin II, inhibiting the increase of transforming growth factor β1 (TGF-β1) and lowering the level of inflammatory mediator of C-reactive protein (CRP) [94]. CSP soluble dietary fiber had protective effects against obesity on HFD-feeding C57BL/6J mice; however, the study also showed that, though CSP could prevent the increase in body weight, it could also result in aggravated liver fibrosis and steatosis [98]. CSP has also been shown to improve microbial community diversity and modulated the overall structure of gut microbiota, thus can be a potential prebiotic agent [96,97].…”
Section: Mushroom Species Containing Bioactive Polysaccharidesmentioning
confidence: 99%
“…Recently, the cordycepin and Cordyceps-derived polysaccharides have been found to attenuate microbiota dysfunction and improve obesity in rat and mice [17,18]. Many experiments have found that Cordyceps-derived polysaccharides have many physiological regulation potentials, including preventing damage of intestinal cells [19] and promoting immunostimulatory activity [20].…”
Section: Introductionmentioning
confidence: 99%